ANALYSIS COMPARATIVE USE OF THE INDONESIAN LANGUAGE TEXT BOOKS FOR X CLASSES PUBLISHED BY YUDHISTIRA AND KEMENDIKBUD IN INDEPENDENT CURICULUM - Syarafina Harahap; Difa Hartati; Putri Alicya; Inayah Hanum; Safinatul Hasanah Harahap (Indonesian language and literature education program Majapahit Islamic University, 2024)
This research aims to determine the comparison of the appropriateness of the contents of textbooks for Class X Indonesian language students at SMA/MA/SMK/MAK published by Yudhistira and the Ministry of Education and Culture. The type of research used in this research is qualitative descriptive research. The research instrument used in this research is the indicators contained in the observed aspects of the suitability of the material, including the suitability of the material to learning outcomes. Accuracy of the material and supporting learning materials. The data analysis techniques used consist of identifying, classifying, interpreting and concluding. The results of this research prove that the Indonesian language student textbooks for Class Both books have a suitable portion to be used to support Indonesian language learning in the independent curriculum in schools, especially for class X students.